Synergistic Effects of Antibiotic Combinations on Carbapenemase Gene Expression in Multidrug-Resistant KPC-Producing Klebsiella pneumoniae - Shafaa hameed kadhim; Hiba Muneer Abdual Hassan Al Kafagi; Sawsan M. Kareem (International Journal of Medical Toxicology and Legal Medicine, 2024)
The healthcare field encounters a major clinical problem given that Multidrug-resistant Klebsiella pneumoniae spreads nosocomial infections while showing resistance against carbapenems which remain the final substances to combat Gram-negative bacteria. This research examined the distribution frequencies of resistance mechanisms and treatment possibilities for 80 Klebsiella pneumoniae clinical isolates obtained from Baghdad, Iraq hospitals. The clinical isolates originating from sputum, urine, wound swabs and burn swabs primarily affected patients with respiratory and urinary tract infections. Through the disc diffusion method investigators found that clinical isolates showed extensive resistance to carbapenems among which ertapenem and imipenem and meropenem exhibited high levels of resistance. The results showed the blaKPC gene in most resistant isolates through PCR detection and the same gene’s expression levels were significantly higher than expression levels of housekeeping 16S rRNA gene when measured by RT-PCR analysis. The characterization results through biochemical analyses revealed that the isolated bacteria were non-motile with positive catalase action and produced oxidase. The combined treatment of carbapenems with aminoglycosides produced superior anti-bacterial results which exceeded those obtained by administering a single antibiotic drug. The obtained research findings indicate that merging antibiotic treatments presents itself as an effective approach against MDR bacterial infections. The research underlines the necessity of implementing complete infection control methods while establishing strong antibiotic stewardship frameworks together with genetic surveillance programs which track antibiotic resistance genes. The identified information will support upcoming investigations into and targeted drug treatments designed to fight MDR Klebsiella pneumoniae infections within healthcare environments.